An analysis of the Treatment of Impotence based on the Theory of Qi and Chemistry of the Five Viscera - Gao, Yiping; Liu, Jianguo (Journal of Contemporary Medical Practice, 2024)
The five organs gasification for the human body fluid, gas, blood, essence and other vital substances all the time transit and mutual transformation process. Penile erectile function is inseparable from the five organs mutual qi function, five organs qi function malfunction of the penis impotence. Blame the heart for the loss of heart and spirit, heart qi insufficiency, heart yang lack of warmth, heart blood deficiency, blame the liver for liver qi stagnation, liver blood deficiency, liver meridian uncomfortable, blame the spleen for the yang deficiency, dampness and evil trapped in the spleen, blame the lungs for the qi insufficiency, the loss of propaganda and purge, and blame the kidney for the yin and yang deficiencies. Through the theory of qi and chemistry of the five viscera, the dysfunction of qi and chemistry of the five viscera is used to describe the pathogenesis of impotence and the selection of treatment prescriptions and medicines, and combined with the joint dialectical treatment of multiple viscera, providing new ideas for the treatment of impotence in Chinese medicine.